How is the math done here:
P0/B0 =( ROE - g)/ (r - g) from this you erive:
P0/B0 = 1 + (ROE - r)/(r - g)
How is the math done here:
P0/B0 =( ROE - g)/ (r - g) from this you erive:
P0/B0 = 1 + (ROE - r)/(r - g)
Damn…my maths is bad!
P0/B0 = 1 + (ROE - r)/(r - g)
P0/B0 = (r - g)/(r - g) + (ROE - r)/(r - g)
P0/B0 =( ROE - g)/ (r - g)
Say what?
P0/B0
= (ROE - g) / (r - g)
= (ROE - g + r - r) / (r - g)
= [(ROE - r) + (r - g)] / (r - g)
= (ROE - r) / (r - g) + (r - g) / (r - g)
= (ROE - r) / (r - g) + 1